2014
DOI: 10.1057/mel.2014.20
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing delay of ships in bulk terminals by simultaneous ship scheduling, stockyard planning and train scheduling

Abstract: Minimizing delay of ships in bulk terminals by simultaneous ship scheduling, stockyard planning and train scheduling S o u d a g a r A . K . I r f a n B a b u a , S a u r a b h P r a t a p a , G e e t L a h o t i a , K i r a n J . F e r n a n d e s b , M a n o j K . T i w a r i a , M a t t h e w M o u n t c a n d Y u X i o n g d A b s t r a c t Because of an increase in population, the demand for coal has drastically risen with millions of tons of coal being imported annually through Indian ports. To accommoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…Ursavas (2014) developed a decision support system to determine simultaneously berthing and quay crane allocation decisions. Babu et al (2014) suggested a model to schedule ships, plan stockyard and rake scheduling to minimize the ship delay at port terminal. However, they have focus on sea side and landside operation, which is beyond the focus of this work.…”
Section: Related Workmentioning
confidence: 99%
“…Ursavas (2014) developed a decision support system to determine simultaneously berthing and quay crane allocation decisions. Babu et al (2014) suggested a model to schedule ships, plan stockyard and rake scheduling to minimize the ship delay at port terminal. However, they have focus on sea side and landside operation, which is beyond the focus of this work.…”
Section: Related Workmentioning
confidence: 99%
“…Such type of costs are mentioned on various other articles within the bounds of maritime transportation. Babu et al (2015) studied ship scheduling problem to cope with the rise in demand in Indian ports. Their problem reduced the delay of ships at port terminals by considering the time window concept and thereby improving the service level.…”
Section: Models With Time Windowsmentioning
confidence: 99%
“…Outside the milk run system, train scheduling is known in the literature. For example, Babu et al (2014) studied train scheduling, ship scheduling and stockyard management in the context of coal imports in port terminals.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%